Return to reason - Toulmin, Stephen, 1922-2009 (Harvard University Press, 2001)
Stephen Toulmin argues that the potential for reason to improve our lives has been hampered by a serious imbalance in our pursuit of knowledge. The centuries-old dominance of rationality, a mathematical mode of reasoning modeled on theory and universal certainties, has diminished the value of reasonableness, a system of humane judgments based on personal experience and practice. To this day, academic disciplines such as economics and professions such as law and medicine often value expert knowledge and abstract models above the testimony of diverse cultures and the practical experience of individuals. Now, at the beginning of a new century, Toulmin sums up a lifetime of distinguished work and issues a powerful call to redress the balance between rationality and reasonableness. His vision does not reject the valuable fruits of science and technology, but requires awareness of the human consequences of our discoveries. Toulmin argues for the need to confront the challenge of an uncertain and unpredictable world, not with inflexible ideologies and abstract theories, but by returning to a more humane and compassionate form of reason, one that accepts the diversity and complexity that is human nature as an essential beginning for all intellectual inquiry.